Demographic Variables Influencing Selective Mutism Among Secondary School Adolescents In Obio/Akpor Local Government Area Of Rivers State - Nwamadi, Love (Advances in Social Sciences Research Journal, 2020)
The study examined demographic variables influencing selective mutism among secondary school adolescents in Obio/Akpor Local Government Area of Rivers State. The study adopted the ex-post-facto research design. Two research questions as well as two corresponding null hypotheses guided the study. The population of the study comprised all 14,784 senior secondary school students (SSS 1, 2 and 3) in the 16 public secondary schools in Obio/Akpor LGA of Rivers State. A sample of 80 secondary school adolescents were randomly and independently selected for the study using the purposive sampling technique. A standardized instrument tagged Skills Deficit Diagnostic Instrument (SDDI), was adopted to collect data for this study. The test re-test method was used to determine reliability and the score obtained was 0.81. Data collected was analyzed using mean, standard deviation and t-test statistics. The finding of the study showed that socioeconomic status significantly influence selective mutism among secondary school adolescents whereas family type did not. Based on the findings of this study, the researcher recommended among others that counseling for adolescents with selective mutism should be encouraged in all schools with the aim of improving adolescents’ mental health and pro-social skills.